Compressive and flexural properties of novel polylactic acid/hydroxyapatite/yttria-stabilized zirconia hybrid nanocomposite scaffold. Issue 4 (4th March 2018) - Ziaee, Farzaneh; Zebarjad, Seyed Mojtaba; Javadpour, Sirus
ABSTRACT: The mechanical property is a crucial factor in the design of bone tissue engineering scaffolds. In the current study, novel PLLA (Poly-L-lactic acid)–Hydroxyapatite (HA)–yttria-stabilized zirconia (YSZ) nanocomposite scaffold with various compositions was prepared and characterized. The effect of HA and YSZ contents on the mechanical behavior of the resultant composites was investigated. TEM micrograph revealed that HA particles are needle-like in shape and nano in size. Scanning electron microscopy (SEM) micrograph also showed that YSZ powder is in granule form and submicron size. SEM disclosed that all scaffolds had a highly interconnected porous structure and X-ray diffractometry revealed that there were some molecular interactions between PLA (Polylactic acid), HA, and YSZ in the composites. The results depicted that introducing YSZ to the nanocomposite leads to a significant increase in compressive strength, modulus, and densification strain. In addition, flexural strength and modulus showed an upward trend by adding YSZ particles to scaffolds. It should be noted that PLA–20%HA–20%YSZ indicates the highest strength and modulus in both compression and bending tests, though, it did not demonstrate the proper strain compared to other scaffolds. Thus, PLA–15%HA–15%YSZ has been reported as the best candidate due to appropriate strength and strain. Also, energy absorption in nanocomposites showed an upward trend by increasing the amount of YSZ particles. It was found that the strength of samples was declined after being soaked in simulated body fluid. However, scaffolds with HA underwent more decrease in strength compared to samples containing YSZ. GRAPHICAL ABSTRACT: